Adaptability and Stability Analyses of Improved Strawberry Genotypes for Tropical Climate - Daniele Aparecida Nascimento; Gabriella Correia Gomes; Luiz Vitor Barbosa de Oliveira; Gabriel Francisco de Paula Gomes; Suzana Tiemi Ivamoto-Suzuki; André Ricardo Ziest; Keny Henrique Mariguele; Sergio Ruffo Roberto; Juliano Tadeu Vilela de Resende (Horticulturae, 2023)
Strawberries are grown worldwide, and the fruit is known for its flavor, pleasant aroma, and the presence of important nutraceutical compounds. Under temperate conditions, the species is octaploid and presents a complex inheritance. Exploring polyploidy in varietal crosses is the main alternative to developing genotypes of high-temperature regions; thus, breeding programs must evaluate the interaction based on parameters, such as the heritability, stability, easy propagation, and adaptability to different soil and climate variations. To estimate the stability and temporal adaptability of pre-selected triple hybrids of day-neutral strawberries, thirty-six experimental genotypes, three commercial genotypes (‘Albion,’ ‘Monterey,’ and ‘Dover’), and four single hybrids (‘RVFS07,’ ‘RVFS06,’ ‘RVDA11,’ and ‘RVCA16’) were evaluated in a protected cultivation from August to February under tropical climate conditions (southern hemisphere) using the mixed linear model (MLM). The genotypes RVFS07M-34, RVFS07M-24, RCDA11M-04, RVFS07M-154, RVFS07M-36, RVFS07M-33, RVFS07M-80, RVFS07M-10, RVDA11M-21, RVDA11M-13, and RVFS06AL-132 had the highest values of total fruit mass, adaptability, and stability. The mean predicted genotypic values of the selected genotypes was 138% higher than the mean of the controls. Therefore, these genotypes have the potential to be released as cultivars.